Comparison of effects of aromatherapy with orange and Citrus aurantium extracts on sleep quality in patients with acute coronary syndrome admitted in the CCU - Rasool Gharaee; Sima Zohari Anboohi; Nahid Saghi; Malihe Nasiri; Yasin Attarroshan; Mohsen Yaghubi (Institue of Medicinal Plants, ACECR, 2020)
Background: Patients with heart problems usually suffer from sleep disorders due to the course of the disease. One of the methods for treating sleep disorders is the use of aromatherapy. Objective: The aim of this study was to investigate and compare effects of aromatherapy with orange and Citrus aurantium extracts on sleep quality in patients with acute coronary syndrome admitted in the CCU. Methods: This clinical trial study was performed on 90 patients. The specimens were divided into three groups of aromatic herbal extracts with orange extract, Citrus aurantium extract and control group. The two groups underwent the treatment with these two extracts. In the control group only the usual care was taken. The data gathering tool was a SMHSQ questionnaire and a demographic profile form. Data were analyzed using SPSS software. Results: The mean sleep quality score in the two intervention groups was significantly lower than the control group (P= 0.0008). However, the mean score of sleep quality in the two groups of aromatherapy was not significant (P= 0.082). Conclusion: The aromatherapy of orange extract and Citrus aurantium improves sleep quality in patients. Each of the extracts can also affect the next dimension of the quality of sleep, which can be used as a topical scent.